The changing trends and tendencies in maternal mortality: a compare and contrast spanning two decades - Govindarajan, Arunadevi; Natarajan, Vijayalakshmi; Ramesh, Sangeetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Though the maternal mortality ratio has been on the constant decline over two decades we shall strive forward to prevent all preventable maternal deaths and we have a long way to reach the SDG 3.1 goal. So, it becomes imperative to further reduce the mortality rates by continuously reviewing and upgrading our health policies. The aim of the study was to compare the trends in maternal mortality in 2002-2011 to the current predicament in 2017- 2019 in our hospital. Methods: Data was collected for all maternal deaths in the Institute of obstetrics and gynaecology, Egmore, Chennai- a centre of excellence for maternal care in South India, in terms of age at time of death, parity, period of death, mode of delivery, the cause of death and the admission to delivery interval and compared between the time periods of 2002-2011 and 2017-2019 to identify the changing patterns. Results: The maternal mortality ratio has consistently declined over the years from 220 in 2002 to 110 in 2019. The age group of 20-29 years and primigravidae continue to amount for most mortality. The postpartum period remains the most susceptible period. There is a significant increase in the number of caesarean deaths (64% from 46%). Significant transition in the cause of death from haemorrhage (20% to 7%) to hypertensive disease of pregnancy (23% to 35%) as leading cause of maternal mortality has been witnessed. Conclusions: Significant difference in the trends over two decades in maternal mortality lies in the fact that the leading cause of maternal mortality has changed from haemorrhage to hypertensive diseases and sepsis and they have continued to occupy the top spots for the past decade. Preventive measures are the solution to reduce maternal mortality due to either of the causes.